Fly ash zeolite-based nano sustained-release material as well as preparation method and application thereof
By flying ash as raw materials, a two-stage fusion process is used to prepare nanocomposite zeolite materials and dopant with micronutrients, the problems of soil degradation and environmental pollution in the use of chemical fertilizers are solved, and efficient and low-cost slow-release fertilizer preparation is achieved.
Patent Information
- Application Number
- CN202410244232.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-04-11
- Filing Date
- 2024-03-04
- Publication Date
- 2025-02-28
AI Technical Summary
Excessive use of existing chemical fertilizers leads to soil degradation, chemical loss and environmental pollution, and modified water coke-based sustained-release materials cannot meet the EU-defined sustained-release performance and high production costs.
Nanocomposite zeolite materials are prepared by a two-stage fusion (melting and hydrothermal) synthesis process using fly ash as raw materials, and the micronutrients required by the plant are doped into the zeolite structure.
It realizes efficient preparation of nano sustained-release materials, meets sustained-release performance standards, reduces production costs, and improves soil microecology health and environmental friendliness.
Smart Images

Figure CN119528164A_ABST
Abstract
Description
[0001] This application claims priority to the prior application No. N2023376234-I filed with the State Intellectual Property Office of China on March 24, 2023, with the invention name “Fly ash zeolite-based nano-sustained-release material and its preparation method and application”; and the prior application No. 202310381676.9 filed with the State Intellectual Property Office of China on April 11, 2023, with the invention name “Fly ash zeolite-based nano-sustained-release material and its preparation method and application”. The entire text of the prior application is incorporated into this application by reference. Technical Field
[0002] The invention belongs to the field of agricultural nano slow-release materials, and relates to a fly ash zeolite-based nano slow-release material, a preparation method thereof and application thereof. Background Art
[0003] Modern agricultural science has a deep understanding of the mechanism behind plant nutrition absorption: the growth of crop yields mainly depends on the absorption of three macronutrients, namely nitrogen (N), phosphorus (P) and potassium (K); and maintaining a healthy soil microecology such as soil rhizosphere microorganisms requires the presence of various beneficial trace mineral nutrients, such as calcium (Ca), magnesium (Mg), iron (Fe), zinc (Zn), molybdenum (Mo), boron (B), selenium (Se), etc. Since the agricultural technology revolution of using plant macronutrient chemicals that emerged with the chemical industry in the last century, it has promoted the global production and application of macronutrient chemicals of the three elements of "N, P, K", forming a fertilizer market with a current production capacity of more than 250 million tons of macronutrient chemicals. Macronutrient chemicals are supplied to agricultural lands around the world in the form of chemical commodities such as nitric acid, ammonium nitrate, synthetic ammonia, urea or sodium nitrate, and are widely applied at different intensities of 100-782 kg per hectare per year; more than half of chemical fertilizers (about 50-80%) are lost due to leaching, discharge or ecological damage (the loss rates of N, P and K chemicals are 40-70, 80-90 and 50-90% respectively). The excessive application of macronutrient fertilizers (including chemicals such as fungicides / pesticides) around the world has caused large-scale degradation of arable land. The large amount of chemical loss has led to eutrophication of surface water and the emergence of polluted dead land; it has caused the content of humus organic carbon in global arable land to drop from 8% at the beginning of the last century to the current 2%.
[0004] In order to solve the problem of chemical loss, nano slow-release materials have emerged as an advanced agricultural fertilizer technology. The European Committee for Standardization working group has defined the standard for "slow-release fertilizers" (SRFs., Slow Release Fertilizers): that is, after the application of "slow-release fertilizers", no more than 15% of the nutrients are released within 24 hours, and the remaining 75% of the nutrients are released within 28 days after application. The inventor has disclosed a sponge-like modified water coke-based slow-release material invention patent prepared from biomass solid waste under [CPCN20111339 Modified water coke and its preparation method and use]; the material has a porous structure and carbon stability similar to soil humin. The modified water coke, together with active substances such as humic acid (preferably artificial humic acid), can be combined into an active humic acid fertilizer similar to soil humification substances. Humic substances in the soil are key substances for maintaining soil ecological balance and controlling the loss of macronutrients. However, modified water coke as a slow-release medium material cannot meet the standards defined by the European Union: that is, "slow-release fertilizer" should release no more than 15% within 1 day after application and 75% within 28 days; and the modified water coke material contains the value of renewable fuel (23MJ / Kg), so the production cost of water coke loaded with macronutrients as a slow-release carrier is high, and it is impossible to form industrial conditions for large-scale centralized production.
[0005] Because, when the humic acid components of organic polymers with fuel value such as peat or lignite are separated, the residue is a stable coal-like substance with the lowest ion exchange acidity, the lowest solubility, and the highest carbon content; this type of residual solid is the same as water coke and soil humin substances, and belongs to the coal-like substances with low ion exchange acidity, low solubility, and more fuel value; this is because the HTC and HTH hydrothermal processes are processes that reduce the oxygen and hydrogen content in biomass to concentrate the chemical energy of carbon bonds. The water coke obtained by the hydrothermal carbonization (HTC) process and the hydrothermal humification (HTH) process is a more valuable biomass renewable fuel than slow-release materials. Therefore, using the residue after the combustion of biomass (including coal) as a raw material to produce slow-release fertilizer medium materials can create higher circular economic value.
[0006] Organic polymers with low mineralization degree such as peat and lignite with fuel value have similar material characteristics to soil humus substances ( Figure 1 ).
[0007] Nearly 60% of China's electricity is obtained by burning coal-like materials. Currently, China produces the largest amount of fly ash in the world (about 600 million tons of fly ash per year). In addition to about 70% of the fly ash used as building materials in cement, concrete, blocks, road cushions, foundation backfill, etc., nearly 200 million tons of untreated fly ash are piled up in abandoned sites every year, and the accumulated untreated fly ash has reached 3 billion tons so far. The trace heavy metals (such as arsenic As, lead Pb, tin Sn, cadmium Cd, etc.) contained in fly ash will continue to diffuse and penetrate into the biosphere through groundwater after a long-term accumulation and enrichment process. The current solution to fly ash is to use it as a raw material for low-value building materials such as cement, concrete, and blocks. The artificial zeolite produced by fly ash through hydrothermal nano-crystalization technology has a controllable nano-scale crystal structure material, and at the same time has a uniformly distributed metal oxide phase inherited from fly ash and transferred to the zeolite matrix. It is generally considered to be a nano-composite material and belongs to the high-value utilization of fly ash regeneration as "smart material". Summary of the invention
[0008] The present invention provides a nano-composite zeolite material synthesized using fly ash as raw material. Preferably, the nano-scale crystal structure of the nano-composite zeolite material is a FAU / Zeolite structure, preferably a FAU / Zeolite Y structure.
[0009] According to an embodiment of the present invention, the nanocomposite zeolite material has micro-mesoporous cage void spaces.
[0010] According to an embodiment of the present invention, the nanocomposite zeolite material is aluminosilicate hydrate.
[0011] According to an embodiment of the present invention, the nanocomposite zeolite material also contains one, two or more micronutrients required by plants among the following elements: magnesium (Mg), iron (Fe), zinc (Zn), molybdenum (Mo), boron (B), selenium (Se), etc. Preferably, the micronutrients required by plants are doped (preferably composite doped) in the zeolite structure.
[0012] According to an embodiment of the present invention, the nanocomposite zeolite material is of a Fugarst zeolite type structure (FAU).
[0013] According to an embodiment of the present invention, the nanocomposite zeolite material has a three-level pore structure:
[0014] The pore size of the first-order pore structure is no more than 10 nm, for example no more than 5 nm, and preferably less than 2 nm (i.e., micropores);
[0015] The pore size of the second-order pore structure (also called mesopore) is equal to or larger than the pore size of the first-order pore structure and does not exceed 50 nm;
[0016] The pore size of the third-level pore structure (also called macropore) is larger than 50 nm, for example, larger than 50 nm and not more than 500 nm, such as 200 nm.
[0017] According to an embodiment of the present invention, the sum of the specific surface areas of the nanocomposite zeolite materials is 150 to 1500 m 2 / g, for example 300~1200m 2 / g, such as 500~1000m 2 / g.
[0018] According to an embodiment of the present invention, the cation exchange capacity (CEC) of the nanocomposite zeolite material is 150-250 cmol (+) / kg, and its activity is much higher than that of soil humin substances.
[0019] According to an embodiment of the present invention, the pore volume of the nanocomposite zeolite material exceeds 50%, for example, exceeds 60%, such as 65-80%.
[0020] According to an embodiment of the present invention, the mass density of the nanocomposite zeolite material is 2.1-2.2 g / cc.
[0021] According to an embodiment of the present invention, the nanocomposite zeolite material has water holding capacity (water holding capacity 50 wt %).
[0022] According to an embodiment of the present invention, the nanocomposite zeolite material is insoluble in water (at any pH).
[0023] According to an embodiment of the present invention, the nanocomposite zeolite material has the characteristics of being resistant to acid and alkali, that is, it is neither soluble in alkali (high pH) nor insoluble in acid (low pH).
[0024] According to an embodiment of the present invention, the fly ash includes but is not limited to one, two or more of the following sources: coal-fired power plants, waste incineration plants, boiler combustion sites, etc., such as ultrafine powder raw materials prepared from fly ash from fly ash landfills and boiler combustion residues; preferably, fly ash generated immediately by pulverized coal boilers in power plants is selected.
[0025] The present invention also provides a method for preparing the above-mentioned nano-composite zeolite material, comprising the following steps: preparing the nano-composite zeolite material through a two-stage synthesis process of fly ash through a double-stage fusion (melting and hydrothermal, i.e., a "two-step method") process.
[0026] According to an embodiment of the present invention, the process of the melting stage includes: mixing fly ash with alkali, heating and melting, grinding, and diluting to obtain a crystallization precursor solution.
[0027] Wherein, the base is selected from a strong base, such as sodium hydroxide.
[0028] The heating and melting process may be performed at a temperature of 500 to 600° C. and for a time of 1 to 9 hours.
[0029] According to an embodiment of the present invention, the method for preparing the nanocomposite zeolite material further comprises subjecting the crystallization precursor solution to ultrasonic treatment and then subjecting the solution to a hydrothermal treatment to obtain the nanocomposite zeolite material.
[0030] According to an embodiment of the present invention, the process of the hydrothermal stage includes: aging and hydrothermal process to obtain crystals; or includes: adding doping elements, aging and hydrothermal process to obtain crystallized crystals of composite doping elements.
[0031] According to an embodiment of the present invention, the hydrothermal stage may include a repeated hydrothermal process of adding N doping elements, where N is an integer equal to or greater than 1, for example, N=1, 2, 3, 4, 5, 6, 7, 8, 9, 10. Specifically, N may be adjusted according to the type and / or content of trace elements required by the composite doped plant ( Figure 2 ).
[0032] According to an embodiment of the present invention, doping elements are added, preferably before the hydrothermal process with N>1 is started, to introduce designated elements so that these elements uniformly form highly active catalytic sites.
[0033] According to an embodiment of the present invention, the doping element is introduced through the following dopants, including but not limited to nanoparticles, alkaline substances and / or crystal nuclei of the one, two or more doping elements.
[0034] Preferably, the doping element is the trace element required by plants as mentioned above.
[0035] According to an embodiment of the present invention, the dopant is added to the crystallization precursor solution, but when N=1 and N≥2, the preparation of the crystallization precursor solution is different:
[0036] When N=1, the crystal precursor solution is obtained by mixing fly ash with alkali, or further mixing with dopants, heating and melting, grinding, and diluting;
[0037] When N≥2, the crystallization precursor solution is obtained by mixing and diluting the filtrate and dopant obtained after the previous hydrothermal crystallization stage, and adding alkali as needed.
[0038] According to an embodiment of the present invention, the mass ratio of the dopant to the crystallization precursor solution is 1:(1-5), for example, 1:1, 1:2, 1:3, 1:4 or 1:5.
[0039] According to an embodiment of the present invention, the temperature of the hydrothermal process is 90 to 170° C. and the time is 2 to 48 hours.
[0040] According to one embodiment of the present invention, the method for preparing the nanocomposite zeolite material comprises the following steps:
[0041] (1) mixing fly ash and alkali, heating and melting, grinding, and diluting to obtain a crystallization precursor solution;
[0042] (2) The crystallization precursor solution is subjected to a hydrothermal process to obtain the nanocomposite zeolite material.
[0043] According to one embodiment of the present invention, the method for preparing the nanocomposite zeolite material comprises the following steps:
[0044] (1) mixing fly ash and alkali, heating and melting, grinding, and diluting to obtain a first crystal precursor solution;
[0045] (2) the first crystal precursor solution is subjected to a hydrothermal process and filtered to obtain crystals and a first filtrate;
[0046] (3) the first filtrate and the dopant containing element 1, and a base as needed, are mixed and diluted to obtain a second crystal precursor solution, and the second crystal precursor solution is subjected to a hydrothermal process and filtered to obtain crystals containing element 1 and a second filtrate;
[0047] (4) The filtrate obtained in the subsequent hydrothermal stage is treated according to step (3), the dopant contains element 2, and crystals containing element 2 and filtrate are obtained; until all the elements to be doped are incorporated into the crystals;
[0048] The element 1 and element 2 are the same or different, preferably different; both are selected from the above-mentioned doping elements;
[0049] The element 1 represents one, two or more elements;
[0050] The element 2 represents one, two or more elements.
[0051] The present invention also provides the use of the nanocomposite zeolite material as a sustained-release medium material, preferably as an agricultural sustained-release medium material.
[0052] In one embodiment, the nanocomposite zeolite material serves as a slow-release medium for macronutrient elements (eg, N, P, K and / or S elements).
[0053] In one embodiment, the nanocomposite zeolite material acts as a slow-release medium for herbicides.
[0054] The present invention also provides a slow-release fertilizer, comprising the nano-composite zeolite material, wherein the nano-composite zeolite material is used as a carrier of active ingredients of the fertilizer.
[0055] According to an embodiment of the present invention, the fertilizer active ingredient is a macronutrient element, such as N, P, K and / or S elements.
[0056] In one embodiment, the nanocomposite zeolite material in the slow-release fertilizer does not contain the specified element.
[0057] In another embodiment, the nanocomposite zeolite material in the slow-release fertilizer contains one, two or more designated elements.
[0058] In yet another embodiment, the nanocomposite zeolite material in the slow-release fertilizer is a mixture of nanocomposite zeolite materials containing different kinds of the specified elements.
[0059] In yet another embodiment, the nanocomposite zeolite material in the slow-release fertilizer is a mixture of a nanocomposite zeolite material that does not contain a designated element and a nanocomposite zeolite material that contains at least one designated element.
[0060] According to an embodiment of the present invention, the slow-release fertilizer is obtained by immersing the nanocomposite zeolite material in a cationic solution containing active ingredients of the fertilizer;
[0061] Preferably, the cations containing active ingredients of fertilizer are provided by compounds such as ammonium nitrate, potassium nitrate, potassium phosphate, synthetic ammonia, urea and / or sodium nitrate;
[0062] Preferably, the mass ratio of the nanocomposite zeolite material to the compound providing cations containing fertilizer active ingredients is (3-10):1, for example 7:1.
[0063] This slow-release fertilizer can completely replace macronutrient (N, P, K, S) chemicals, i.e. commercial fertilizers in the form of potassium nitrate, ammonium nitrate, potassium phosphate, synthetic ammonia, urea or sodium nitrate.
[0064] According to an embodiment of the present invention, the structure (whole structure and pore structure) and specific surface area of the slow-release fertilizer are substantially consistent with those of the nanocomposite zeolite material.
[0065] According to an embodiment of the present invention, the slow-release fertilizer may be a solid-liquid mixed fertilizer or a solid fertilizer.
[0066] The invention also provides a slow-release herbicide, which contains the nano composite zeolite material and the herbicide.
[0067] The present invention also provides the use of the above slow-release fertilizer or slow-release herbicide in the fields of soil and / or planting. For example, it can be used as soil fertilizer, to promote the ecological balance of soil microorganisms and soil animals, to promote the degradation or inactivation of toxic substances in the soil, to improve soil pH, plant fertilizer, to promote plant growth, and to irrigate plants. For example, the fertility of the slow-release fertilizer containing macronutrient cations according to the stoichiometric leaching amount is at least twice the fertility of the stoichiometric cation of the same macronutrient chemical.
[0068] According to an embodiment of the present invention, the slow-release fertilizer is used as a soil fertilizer and / or a plant fertilizer.
[0069] The present invention also provides a soil fertilizer, which contains the nano-composite zeolite material, wherein the soil fertilizer can be a liquid-solid mixed fertilizer or a solid fertilizer.
[0070] The present invention also provides a method for preparing the soil fertilizer, which comprises preparing the soil fertilizer from raw materials containing the nano composite zeolite material.
[0071] The present invention also provides a soil conditioner, which contains the nano-composite zeolite material, wherein the soil conditioner can be a liquid-solid mixed conditioner or a solid conditioner.
[0072] In one embodiment, the soil is sandy soil. When used to improve sandy soil, adding the soil conditioner containing the nanocomposite zeolite material can reduce the ammonia volatilization of sandy soil by 8%, and increase the water retention rate of sandy soil by 10% and the available water storage capacity by 15%.
[0073] In some embodiments, the soil conditioner is used to adjust soil physical properties, such as increasing soil water holding capacity and reducing soil water salinity.
[0074] In some embodiments, the soil conditioner is used to repair contaminated soil. In some soils contaminated by heavy metals or radioactive nuclei, nanocomposite zeolite materials doped with special elements can be used to repair radioactive contamination.
[0075] The present invention also provides a method for preparing the soil conditioner, which comprises preparing the soil conditioner from raw materials containing the nano composite zeolite material.
[0076] The present invention also provides a plant fertilizer, which contains the nano-composite zeolite material, wherein the plant fertilizer can be a liquid-solid mixed fertilizer or a solid fertilizer.
[0077] The present invention also provides a method for preparing the plant fertilizer, which comprises preparing the plant fertilizer from a raw material containing the nano-composite zeolite material.
[0078] The invention also provides a plant growth agent containing the nano composite zeolite material.
[0079] The present invention also provides a method for preparing the plant growth agent, which comprises preparing the plant growth agent from a raw material containing the nano-composite zeolite material.
[0080] The present invention also provides the use of the nanocomposite zeolite material in wastewater treatment, for example, removing ammonia and / or heavy metal ions in wastewater.
[0081] The invention also provides a wastewater treatment agent containing the nano composite zeolite material.
[0082] The inventor believes that the large-scale use of fly ash from the combustion of biomass and other coal-like materials to synthesize slow-release fertilizer media materials for advanced agriculture will produce a higher value circular economy effect, because:
[0083] (1) Maintaining healthy plant growth depends on the ecological balance of soil microorganisms and requires a variety of trace beneficial mineral elements that can degrade and inactivate toxic substances. Fly ash is the residue left after high-temperature incineration of biomass or coal-like materials. In addition to mainly containing aluminum (Al) and silicon (Si), it is also rich in alkali metals, alkaline earth metals, transition metals and a variety of other trace mineral metal elements. Some beneficial mineral elements that originated in ancient times and were selectively absorbed by plants during their growth stage, such as magnesium (Mg), iron (Fe), zinc (Zn), molybdenum (Mo), boron (B), selenium (Se), etc., can be recycled and reused in the process of synthesizing slow-release materials from fly ash. The beneficial mineral elements can be "intelligently" quantitatively added into the structural framework of the slow-release material through the present invention, and can be reapplied to nourish the soil microecology.
[0084] (2) Natural zeolite is a kind of micro-mesoporous cage multi-channel high surface area aluminosilicate (xAl2O3·ySiO2) material. The ionic potential outside the zeolite structure framework is higher than that inside the zeolite structure framework. The accumulation of small-sized high-field strength cations and water cations in the structure framework increases the hydration capacity of the zeolite material. This capacity can greatly reduce the amount of pesticides and fertilizers required in the soil. For example, zeolite material only passes NH4 + Cationic leaching can directly improve soil nutrient utilization and reduce the loss of macronutrient nitrogen. The main components of combustion fly ash are SiO2 and Al2O3, which can be used to synthesize fly ash zeolite-based materials with the same structure as natural zeolite and cation exchange capacity; as an agricultural slow-release fertilizer material, it can control the loading and release of macronutrient elements (N, P, K, S).
[0085] (3) Soil salinization is characterized by the Na + and Ca 2+High in content. So zeolite is loaded with macronutrients: K + or NH 4+ After that, the Na in soil water can be exchanged in turn. + , Ca 2+ , which is beneficial to reduce the Na + , Ca 2+ The preferred order of cation exchange in FAU / Zeolite cage structure: Na + >K + >Ag + >NH 4+ >Ca 2+ >Sr 2+ >Li 2+ , is the driving force of Na + , Ca 2+ The main reason for the reduction is that the FAU zeolite cage structure particularly prefers Na + , so the K loaded in part of the cage + Ions will actively exchange the abundant Na + ions, while some Na + Ion exchange for K + Ions; K in soil water + Ions also convert Ca in calcium phosphate ore 2+ Exchanged into water; calcium ions Ca in water 2+ will be active (according to FAU zeolite Ca 2+ Preferred order) and K loaded in the zeolite structure cage + The ions are exchanged again, so the water gradually gets more K + Ions. The potassium ions loaded in the cage structure are exchanged to obtain Na + and Ca 2+ , reducing Na in soil water + and Ca 2+ Therefore, the large-scale use of fly ash zeolite-based macronutrient slow-release fertilizers has the effect of reducing soil water salinity and soil compaction ( Figure 3 ).
[0086] (4) The global environmental burden of fly ash output from coal-fired power boilers is huge, and is of the same order of magnitude as the global use of agricultural macronutrient chemicals. Therefore, large-scale production of fly ash zeolite-based materials will rapidly reduce the environmental accumulation of fly ash, while meeting the demand for agricultural macronutrient slow-release fertilizer media, and promoting the realization of the huge environmental benefits of the widespread application of nano slow-release fertilizers in advanced agriculture.
[0087] Beneficial effects of the present invention:
[0088] (1) The fly ash zeolite-based macronutrient slow-release fertilizer of the present invention can completely replace traditional fertilizers and has the following significant effects compared with traditional chemical fertilizers: (i) the crop absorption rate and utilization rate of the relevant macronutrients are increased by not less than 200% (theoretical value is greater than 700%); (ii) the loss of the relevant macronutrients is reduced by not less than 50% (theoretical value is greater than 80%), and environmental pollution is significantly reduced; (iii) the diffusion rate and solubility of the macronutrients in the organic polymer colloids of the soil are improved (without stoichiometric calculation); (iv) the macronutrient load of the present invention can be controlled and released according to the needs of plant growth; (v) the high specific surface area will use less fertilizer to achieve healthier ecological activity of the soil (without stoichiometric calculation); (vi) the water-retaining structure in the form of a micro-mesoporous cage (theoretical value of material water retention rate>5) can reduce the salinity and alkalinity of soil water, reduce the degree of soil compaction, and help create a sustainable soil environment.
[0089] (2) The fly ash zeolite slow-release medium material prepared by the present invention can also be used for the treatment of organic fertilizer application on farmland and environmental management; the zeolite material synthesized from fly ash can be used as an effective additive to control odor, and the high specific surface area can adsorb volatile substances such as acetic acid, butyric acid, isovaleric acid, scutellaria baicalensis, and feces to improve the effectiveness of fertilizers. The adsorption of zeolite materials can reduce the loss of ammonia in farmyard manure and reduce the impact of nitrogen on the environment. The fly ash-based zeolite material mixed with organic matter can also obtain mature compost with good agronomic performance.
[0090] (3) The fly ash zeolite-based slow-release medium material prepared by the present invention can also be used for nitrogen management of farmland soil environment: although nitrogen nutrient fertilizers are widely used in all crops and planting systems, their utilization efficiency is only 30-40%. Zeolite-based materials can be directly applied to animal digestive waste, for example, to remove unpleasant odors in cattle pens, stables and pig pens, and can be used for the collection of animal fertilizer raw materials in agricultural livestock and poultry farming. Fly ash zeolite-based materials will reduce soil urease activity and improve nitrogen utilization efficiency in paddy fields, and ensure effective phosphorus and nitrates in the soil. Fly ash zeolite slow-release medium materials can adsorb and retain a large amount of ammonium ions, acting as a good adsorbent for nitrates, reducing environmental leaching of nitrates and ammonium salts.
[0091] (3) The fly ash zeolite-based slow-release medium material prepared by the present invention can manage phosphorus in farmland soil environment; the cation exchange fertilizer composed of fly ash zeolite-based material and rock phosphate: Ca in soil environment 2+ will be directly exchanged into the structure of the fly ash zeolite-based material in response to plant uptake of nutrient cations (NH4 + or K +) growth requirements, enhancing the dissolution of rock phosphates in the soil. A large number of experiments have shown that ammonium-containing zeolite-based materials increase the solubility of phosphate minerals in animal ashes and can promote the dissolution of rock phosphates contained in all types of soils.
[0092] (4) The fly ash zeolite-based slow-release medium material prepared by the present invention can carry out centralized slow-release management of a variety of nutrients; the outstanding function of the fly ash zeolite-based material is the ability of nano-enhanced nitrogen capture, storage and release, which can adsorb molecules at relatively low pressures. Adding fly ash zeolite-based materials to organic matrices can directly improve soil fertility. Fly ash zeolite-based materials, even as coating materials, have the potential to absorb and retain water, and can also improve the storage of macro-mineral elements N, P, and K. Therefore, they can also play a role in delaying the release of N, P, and K in sandy soils. As a sandy soil conditioner, the addition of fly ash zeolite-based materials can reduce the ammonia volatilization of sandy soil by 8%, and at the same time increase the water retention rate of sandy soil by 10% and the available water storage capacity by 15%.
[0093] (5) The fly ash zeolite-based slow-release medium material prepared by the present invention can also manage the slow release of herbicides: when organic matter exists in the macroporous void space within the fly ash zeolite-based material, the adsorption capacity of the zeolite will be better, and it can be combined with the formulation of soil clay mineral slow-release herbicides. When the zeolite material contains the herbicide paraquat in the microstructure, the surface of paraquat will be modified. The fly ash zeolite-based material uses a selected catalyst load to enhance the activity of the herbicide isopropanal and increase visible light absorption.
[0094] (6) The fly ash zeolite-based slow-release medium material prepared by the present invention manages the physical properties of the soil; the fly ash zeolite-based material can improve the physical properties of the soil. The high porosity of its crystal structure can accommodate more than half of its weight in water. The process of water molecules being evaporated or reabsorbed will not damage the pore structure. It ensures the existence of micro "water pools" containing water in the soil, providing long-term moisture during the soil dry period to help plants resist drought; the fly ash zeolite-based material can also promote rapid rewetting and improve the lateral diffusion of water to the root zone during irrigation, which can save water resources for irrigation. The fly ash zeolite-based material after mixing and supplementing with sand can also increase the available water for plants by 50%.
[0095] (7) The fly ash zeolite-based slow-release medium material prepared by the present invention can be used as a cheap repair material for soil pollution; in some soils contaminated by heavy metals or radioactive nuclei, functional modified materials doped with special elements can be used to repair radioactive pollution.
[0096] (8) The fly ash zeolite-based slow-release medium material prepared by the present invention is a long-term soil conditioner: the structure of the fly ash zeolite-based material is composed of cage-like polyhedral units with high cation exchange capacity and internal pores in the crystal lattice, and the material has high water adsorption and nutrient retention characteristics. The fly ash zeolite-based material has good stability and will not decompose over time. Its long-term presence in the soil improves the stability of retained nutrients. The addition of fly ash zeolite-based materials to the soil can significantly reduce water and fertilizer costs by retaining beneficial nutrients in the root system. The porous crystal structure of the zeolite-based material helps to keep the soil aerated, moist, and active for a long time.
[0097] (9) The fly ash zeolite-based sustained-release medium material prepared by the present invention also has an additional wastewater treatment function; because the adsorption properties of the zeolite-based material can also be used to remove ammonia in wastewater; the material can effectively and selectively remove ammonium cations in wastewater; it is an ideal material for removing heavy metal ions from wastewater, and its relatively low cost and the harmless nature of the exchangeable ions are beneficial to the overall ecological and biological environment.
[0098] The above-mentioned fly ash zeolite-based sustained-release medium material, zeolite-based material and fly ash zeolite-based material all refer to nanocomposite zeolite materials.
[0099] The fly ash zeolite-based macronutrient slow-release fertilizer is a slow-release fertilizer comprising a nanocomposite zeolite material and macronutrients. BRIEF DESCRIPTION OF THE DRAWINGS
[0100] Figure 1 The chemical properties of humic substances;
[0101] Figure 2 The figure is a process flow chart for preparing nanocomposite zeolite materials;
[0102] Figure 3 Schematic diagram of the nanocomposite zeolite material for reducing soil water salinity;
[0103] Figure 4 The adsorption capacity of the nanocomposite zeolite material of Example 1 to ammonium ions;
[0104] Figure 5 This is the adsorption capacity of the nanocomposite zeolite material of Example 1 for ammonia nitrogen and K ions. DETAILED DESCRIPTION
[0105] The technical scheme of the present invention will be further described in detail below in conjunction with specific embodiments. It should be understood that the following embodiments are only exemplary descriptions and explanations of the present invention and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are included in the scope that the present invention is intended to protect.
[0106] Unless otherwise specified, the raw materials and reagents used in the following examples are commercially available or can be prepared by known methods.
[0107] Example 1
[0108] A nanocomposite zeolite material prepared by a two-step process of melting and hydrothermal has a zeolite structure formed with fly ash as raw material. The material has a micro-mesoporous crystal cage structure of a certain scale, and the certain scale is: the structural parameters of the FAU / Zeilite Y-type micro-mesoporous crystal cage.
[0109] The nanocomposite zeolite material has a three-level pore structure:
[0110] The pore size of the first-level pore structure is 5 nm;
[0111] The pore size of the second-order pore structure (also called mesopores) is 50 nm;
[0112] The pore size of the tertiary pore structure (also called macropores) is 100 nm.
[0113] The sum of the specific surface areas of the nanocomposite zeolite material is 150 to 1500 m 2 / g, for example 300~1200m 2 / g, such as 500~1000m 2 / g.
[0114] The cation exchange capacity (CEC) strength of the nanocomposite zeolite material is 150-250 cmol (+) / kg.
[0115] The pore volume of the nanocomposite zeolite material accounts for more than 50%, such as more than 60%, such as 65-80%.
[0116] The mass density of the nanocomposite zeolite material is 2.1-2.2 g / cc.
[0117] The nanocomposite zeolite material has water holding performance (also called water retention performance).
[0118] The nanocomposite zeolite material is insoluble in water (at any pH).
[0119] The nanocomposite zeolite material has the characteristics of being resistant to acid and alkali, that is, it is neither soluble in alkali (high pH) nor in acid (low pH).
[0120] The yield of nano-composite zeolite material obtained by melting and hydrothermal two-stage process (two-step method) of fly ash raw materials (1<silicon-aluminum ratio<5, calcium content<10%) is not less than 50%.
[0121] The adsorption characteristics of the prepared nanocomposite zeolite material were used to test the loading capacity of macroelements (N, K) cations; ammonium ions NH4 + , ammonia nitrogen (ammonium chloride NH4Cl) and potassium ions (potassium chloride KCl) are as follows:
[0122] 1) Ammonium ion: The Langmuir method was used to study the adsorption capacity of the prepared nanocomposite zeolite material for ammonium ions: 0.5g of zeolite with a particle size of 20-30 mesh was added to 25ml of 5000mg / L ammonia nitrogen solution (prepared with ammonium chloride). The ammonia nitrogen solution was adjusted to different pH values with HCl and NaOH respectively. The adsorption was carried out under oscillation at room temperature for 4h. After the adsorption was completed, the supernatant was removed to determine the ammonia nitrogen content, and the unit adsorption amount of ammonia nitrogen by the zeolite (mg / kg) was calculated. The calculation result is as follows: Figure 4 As shown in the table below, it is inhibited under acidic conditions, and the adsorption capacity increases with the increase in pH to neutral conditions. The ammonium adsorption capacity was measured to be 110700 mg / kg at a pH of 7.3.
[0123] pH Ammonium adsorption capacity (mg / kg) 4.3 34900 5.3 58800 6.3 83300 7.3 110700
[0124] 2) Ammonia nitrogen and potassium ions: 0.5g zeolite was added to 25ml ammonium chloride and potassium chloride solutions respectively, and the mixture was adsorbed by oscillation for 4h. After the adsorption was completed, the unit adsorption capacity of the zeolite was measured. The results were as follows: Figure 5 and the table below:
[0125]
[0126]
[0127] Example 2 Preparation method for improving the yield of nanocomposite zeolite material of Example 1
[0128] The fly ash from coal-fired power boilers is used as raw material. The crystal precursor solution is subjected to a two-step process of melting and hydrothermal treatment (two-step method). An ultrasonic treatment step is added to the crystallization precursor solution, and then the solution is subjected to a hydrothermal treatment step to obtain the crystallization precursor solution.
[0129] The melting operation is as follows: mix the fly ash with sodium hydroxide, heat and melt at 500-600° C. for 1-9 hours; grind and dilute to 1-2.5 mol / L to obtain a crystal precursor solution.
[0130] The hydrothermal operation is as follows: the crystal precursor solution is subjected to ultrasonic treatment for 15 to 90 minutes, and then hydrothermally activated at 90 to 170° C. for 2 to 48 hours, and the crystal product is filtered and washed to obtain the nanocomposite zeolite material.
[0131] The yield of the filtered crystallized product, ie, the nanocomposite zeolite material, in Example 2 is 8-15% higher than that in Example 1.
[0132] Example 3
[0133] A nanocomposite zeolite material has a zeolite structure formed from fly ash as a raw material, and micronutrients required by plants that are adjusted and doped as needed: magnesium (Mg), iron (Fe), zinc (Zn), cerium (Ce), molybdenum (Mo), boron (B) and / or selenium (Se), these elements form highly active catalytic sites. In one embodiment, these adjusted doped elements exist in the form of nanoparticle crystal nuclei.
[0134] The material has a micro-mesoporous crystal cage structure of a certain scale, and the certain scale is: structural parameters of a FAU / Zeilite Y-type micro-mesoporous crystal cage.
[0135] The nanocomposite zeolite material has a three-level pore structure:
[0136] The pore size of the first-level pore structure is 5 nm;
[0137] The pore size of the second-order pore structure (also called mesopores) is 50 nm;
[0138] The pore size of the tertiary pore structure (also called macropores) is 100 nm.
[0139] The sum of the specific surface areas of the nanocomposite zeolite material is 150 to 1500 m 2 / g, for example 300~1200m 2 / g, such as 500~1000m 2 / g.
[0140] The cation exchange capacity (CEC) strength of the nanocomposite zeolite material is 150-250 cmol (+) / kg.
[0141] The pore volume of the nanocomposite zeolite material accounts for more than 50%, such as more than 60%, such as 65-80%.
[0142] The mass density of the nanocomposite zeolite material is 2.1-2.2 g / cc.
[0143] The nanocomposite zeolite material has water holding performance (also called water retention performance).
[0144] The nanocomposite zeolite material is insoluble in water (at any pH).
[0145] The nanocomposite zeolite material has the characteristics of being resistant to acid and alkali, that is, it is neither soluble in alkali (high pH) nor in acid (low pH).
[0146] This example uses a multi-step synthesis method derived from the "two-step method" ( Figure 2), the fly ash raw material is prepared into a nano-composite zeolite material containing a specified combination of beneficial trace elements; since the beneficial trace elements originally contained in the fly ash raw material may be insufficient to meet the needs of specific planting soils and crops, the nano-composite zeolite material prepared by the multi-step synthesis method of this embodiment can adjust the doping content of the beneficial trace elements in the zeolite material according to a specified combination of beneficial trace mineral elements different from the original fly ash raw material.
[0147] For example, in this embodiment: the doping amounts of zinc (Zn), cerium (Ce) and iron (Fe) are increased, and a nanocomposite zeolite material with quantitatively increased doping amounts of the three specified metal elements is prepared in a "multi-step synthesis method".
[0148] Take 10g of fly ash and add 10g of alkali (NaOH) to mix, and heat and melt in a muffle furnace at 600°C for 1h. After cooling the sample to room temperature, grind it, add 200ml of water, 10g of NaOH, 10g of sodium silicate, etc. to dilute it to obtain a crystallization precursor solution, and then hydrothermally react it at 100°C for 8h; solid-liquid separation, add 3.3g of raw ash and 3.3g of alkali (NaOH) to the first crystallization precursor solution, and then hydrothermally react it at 100°C for 8h to obtain "undoped zeolite", which is recorded as sample F0.
[0149] Take 10g of fly ash and add 10g of alkali (NaOH) to mix, and heat and melt in a muffle furnace at a constant temperature of 600 for 1h. After cooling the sample to room temperature, crush and grind it, add 200ml of water, 10g of NaOH, 10g of sodium silicate, etc. to dilute it to obtain a crystallization precursor solution, and hydrothermally react at 100℃ for 8h; solid-liquid separation, add 3.3g of nano-metal oxides (Fe2O3, ZnO, CeO2 in solid powder / inorganic salt state) and 3.3g of alkali (NaOH) to the first crystallization precursor solution, and hydrothermally react at 100℃ for 8h to obtain "zeolites doped with Fe2O3, ZnO, CeO2, etc.", recorded as F(Fe), F(Zn), and F(Ce).
[0150] The metal doping amount in the zeolite material before and after the metal element doping was measured, see the following table:
[0151] sample Zn(mg / g) Ce(mg / g) Fe(mg / g) F0 0.71 0.16 69.50 F(Fe) 0.59 0.09 541.82 F(Zn) 735.63 0.08 0.32 F(Ce) 0.14 205.57 0.31
[0152] Example 4: The parallel preparation method of the nanocomposite zeolite material in Example 3 can be changed to a sequential doping addition method.
[0153] Example 4 Sequential doping preparation method of nanocomposite zeolite material (see Figure 2 ) comprises the following steps:
[0154] (1) fly ash is mixed with sodium hydroxide, heated to 500-600° C. for melting for 1-9 hours; ground and diluted to 1-2.5 mol / L to obtain a first crystal precursor solution;
[0155] (2) the first crystal precursor solution is subjected to a zeolite process in a hydrothermal stage and filtered to obtain crystals and a first filtrate;
[0156] The specific operation of the hydrothermal stage is as follows: the crystal precursor solution is subjected to ultrasonic treatment for 15 to 90 minutes, then hydrothermally activated at 90 to 170° C. for 2 to 48 hours, filtered to obtain a crystal product and a first filtrate, and the product is washed and collected;
[0157] (3) the first filtrate is mixed and diluted with a dopant containing the designated element 1, and sodium hydroxide is added or not added as needed to obtain a second crystal precursor solution, the second crystal precursor solution is subjected to a zeolite process in a hydrothermal stage, and filtered to obtain crystals containing the designated element 1 and a second filtrate;
[0158] (4) The filtrate obtained in the subsequent hydrothermal stage is treated according to step (3), and the dopant contains the specified element 2, thereby obtaining a crystal and a filtrate containing the specified element 2; and the process ends when all the elements to be doped are doped into the crystal;
[0159] The designated element 1 and the designated element 2 are different and are selected from the micronutrients required by plants: magnesium (Mg), iron (Fe), zinc (Zn), cerium (Ce), molybdenum (Mo), boron (B) and / or selenium (Se);
[0160] The designated element 1 represents one, two or more elements;
[0161] The designated element 2 represents one, two or more elements;
[0162] The dopant is a nanoparticle, an alkaline substance and / or a crystal nucleus containing a specified element;
[0163] The mass ratio of the dopant to the crystallization precursor solution is 1:(1-5), for example, 1:1, 1:2, 1:3, 1:4 or 1:5.
[0164] Example 5 Another preparation method for improving the yield of the nanocomposite zeolite material of Example 3
[0165] Example 3 The preparation method of the nanocomposite zeolite material comprises the following steps:
[0166] (1) fly ash is mixed with sodium hydroxide, heated to 500-600° C. for melting for 1-9 hours; ground, diluted to 1-2.5 mol / L, and doped with a dopant containing a specified element to obtain a crystallization precursor solution;
[0167] (2) The crystallization precursor solution is subjected to a zeolite process in a hydrothermal stage to obtain the nanocomposite zeolite material;
[0168] The specific operation of the hydrothermal stage is as follows: the crystal precursor solution is subjected to ultrasonic treatment for 15 to 90 minutes, and then hydrothermally activated at 90 to 170° C. for 2 to 48 hours, filtered to obtain a crystal product and a filtrate, and the product is washed and collected;
[0169] The dopant is a nanoparticle, an alkaline substance and / or a crystal nucleus containing a specified element;
[0170] The mass ratio of the dopant to the crystallization precursor solution is 1:(1-5), for example, 1:1, 1:2, 1:3, 1:4 or 1:5;
[0171] The designated element is selected from the group consisting of micronutrients required by plants: magnesium (Mg), iron (Fe), zinc (Zn), cerium (Ce), molybdenum (Mo), boron (B) and / or selenium (Se).
[0172] The nanocomposite zeolite material of the above specified element combination can be used as a slow-release medium in the fields of soil, planting, etc. For example, it can be used as soil fertilizer, promote the ecological balance of soil microorganisms and soil animals, promote the degradation or inactivation of toxic substances in the soil, improve soil pH, plant fertilizer, promote plant growth, plant irrigation and form a soil nutrient environment of specified elements, etc.
[0173] Example 6
[0174] A slow-release fertilizer comprising the nanocomposite zeolite material of Example 1 as a carrier of an active ingredient of the fertilizer;
[0175] The active ingredients of the fertilizer are macronutrient elements: N, P, K and / or S elements, which are impregnated in the space of the honeycomb micro-mesoporous cage channel of the nano-composite zeolite material in a cation state.
[0176] The slow-release fertilizer is obtained by immersing the nanocomposite zeolite material in a cationic solution containing active ingredients of the fertilizer;
[0177] The cations containing active ingredients of the fertilizer are provided by compounds such as ammonium nitrate, potassium nitrate, potassium phosphate, synthetic ammonia, urea and / or sodium nitrate;
[0178] The mass ratio of the nanocomposite zeolite material to the compound providing cations containing active fertilizer ingredients is 7:1.
[0179] The structure (overall structure and pore structure) and specific surface area of the slow-release fertilizer are substantially consistent with those of the nanocomposite zeolite material in Example 1.
[0180] The slow-release fertilizer can completely replace macronutrient (N, P, K and / or S) chemicals, i.e. commercial fertilizers in the form of potassium nitrate, ammonium nitrate, potassium phosphate, synthetic ammonia, urea or sodium nitrate.
[0181] According to needs, the slow-release fertilizer is a solid-liquid mixed fertilizer or a solid fertilizer, which is used as soil fertilizer and / or plant fertilizer.
[0182] When it is a solid-liquid mixed fertilizer, it contains the nanocomposite zeolite material of Example 1 and the impregnated cation solution of macronutrients (containing N, P, K and / or S compound elements). Preferably, the hydrothermal stage of the two-step method can couple and enhance the K macronutrient element, that is, introduce the macronutrient K as a coupling activator of the precursor solution, that is, enhance the chemical elements of the K composite fertilizer with a slow release design concentration.
[0183] Take 10g of fly ash and add 10g of alkali (NaOH) to mix, and heat and melt in a muffle furnace at 600°C for 1h. After cooling the sample to room temperature, grind it, add 200ml of water, 10g of NaOH, 10g of sodium silicate, etc. to dilute it to obtain a crystallization precursor solution, and then hydrothermally react it at 100°C for 8h; solid-liquid separation, add 3.3g of raw ash and 3.3g of alkali (NaOH) to the first crystallization precursor solution, and then hydrothermally react it at 100°C for 8h to obtain "undoped zeolite", which is recorded as sample F0.
[0184] Take 10g of fly ash and add 10g of alkali (NaOH) to mix, and heat and melt in a muffle furnace at a constant temperature of 600 for 1h. After cooling the sample to room temperature, grind it, add 200ml of water, 10g of NaOH, 10g of sodium silicate, etc. to dilute it to obtain a crystallization precursor solution, and hydrothermally react at 100℃ for 8h; solid-liquid separation, add 3.3g of raw ash and 3.3g of alkali (KOH) to the first crystallization precursor solution, and hydrothermally react at 100℃ for 8h to obtain "K nutrient zeolite", which is recorded as sample F(K).
[0185] The increase in potassium K in the zeolite material before and after the introduction of macronutrients was measured, as shown in the following table:
[0186] sample K(mg / g) F0 0.82 F(K) 31.69
[0187] Example 7
[0188] A slow-release fertilizer comprising the nanocomposite zeolite material of Example 3 as a carrier of an active ingredient of the fertilizer;
[0189] The active ingredients of the fertilizer are macronutrient elements: N, P, K and / or S elements, which are impregnated in the space of the honeycomb micro-mesoporous cage channel of the nano-composite zeolite material in a cation state.
[0190] The slow-release fertilizer is obtained by immersing the nanocomposite zeolite material in a cationic solution containing active ingredients of the fertilizer;
[0191] The cations containing active ingredients of the fertilizer are provided by compounds such as ammonium nitrate, potassium nitrate, potassium phosphate, synthetic ammonia, urea and / or sodium nitrate;
[0192] The mass ratio of the nanocomposite zeolite material to the compound providing cations containing active fertilizer ingredients is 7:1.
[0193] The structure (overall structure and pore structure) and specific surface area of the slow-release fertilizer are substantially consistent with those of the nanocomposite zeolite material in Example 3.
[0194] The slow-release fertilizer can completely replace macronutrient (N, P, K and / or S) chemicals, i.e. commercial fertilizers in the form of potassium nitrate, ammonium nitrate, potassium phosphate, synthetic ammonia, urea or sodium nitrate.
[0195] According to needs, the slow-release fertilizer is a solid-liquid mixed fertilizer or a solid fertilizer, which is used as soil fertilizer and / or plant fertilizer.
[0196] When it is a solid-liquid mixed fertilizer, it contains the nanocomposite zeolite material of Example 3 and the impregnated cation solution of macronutrients (containing N, P, K and / or S compound elements). Preferably, the concentration of the K macronutrient element and the specified trace mineral element can be coupled and doped to adjust, for example, according to the embodiment of the preparation of the above-mentioned macronutrient impregnated slow-release fertilizer product, the macronutrient K is introduced as a coupling activator of the precursor solution, that is, the coupling and doping adjustment of the macronutrient K is performed on the specified beneficial trace metal elements, such as the enhancement of the chemical elements of the slow-release designed concentration of K composite fertilizer.
[0197] In addition, because nitrogen fertilizers are widely used in all crops and planting systems, but their utilization efficiency is only 30-40%, the strong adsorption of fly ash zeolite-based slow-release medium materials can also be directly used for nitrogen management in farmland soil environments. The following nanocomposite zeolite materials were added to different soils to test the adsorption + slow-release effect of urea fertilization.
[0198] The nanocomposite zeolite material crystalline powders of Examples 1 to 5 above were prepared, and the urea fertilizer was in the form of a powder with a particle size of 80 mesh. Urea and zeolite were stirred in different soil samples until homogeneous, and the data were measured after 7 days of cultivation. The analysis of the released nitrogen content in the urea slow-release fertilizer was obtained using the Kjeldahl method, and the results are shown in the following table.
[0199] Nitrogen content released from urea slow-release fertilizer before and after zeolite incubation in different soil samples
[0200] Soil samples Before adding zeolite After adding zeolite Sandy loam 33.23% 0.422% Paddy soil 42.43% 0.512% Red soil 39.81% 0.493% Brown soil 36.81% 0.432%
[0201] According to the data of this example, fly ash zeolite-based materials can reduce soil urease activity and improve soil nitrogen utilization efficiency. They can adsorb and retain a large amount of ammonium ions, serve as a good adsorbent for nitrate, and reduce environmental leaching of nitrate and ammonium salts.
Claims
1. A nanocomposite zeolite material, characterized in that: The nanocomposite zeolite material has a zeolite structure formed using fly ash as raw material; Preferably, the zeolite structure is a FAU / Zeolite structure, and more preferably a FAU / Zeolite Y-type structure. Preferably, the nanocomposite zeolite material has micro-mesoporous cage void spaces. Preferably, the nanocomposite zeolite material is aluminosilicate hydrate.
2. The nanocomposite zeolite material according to claim 1, characterized in that: The nanocomposite zeolite material also contains one, two or more micronutrients required by plants: magnesium (Mg), iron (Fe), zinc (Zn), molybdenum (Mo), boron (B), selenium (Se), etc. Preferably, the micronutrients required by plants are doped with designated trace elements (preferably K-coupled doping) in the zeolite structure.
3. The nanocomposite zeolite material according to claim 1 or 2, characterized in that: The nanocomposite zeolite material has a three-level pore structure: The pore size of the first-order pore structure is no more than 10 nm, for example no more than 5 nm, and preferably less than 2 nm (i.e., micropores); The pore size of the second-order pore structure (also called mesopore) is equal to or larger than the pore size of the first-order pore structure and does not exceed 50 nm; The pore size of the third-level pore structure (also called macropore) is larger than 50 nm, for example, larger than 50 nm and not more than 500 nm, such as 200 nm.
4. The nanocomposite zeolite material according to any one of claims 1 to 3, characterized in that: The sum of the specific surface areas of the nanocomposite zeolite material is 150 to 1500 m 2 / g; and / or, the cation exchange capacity of the nanocomposite zeolite material is 150-250 cmol(+) / kg; and / or, the pore volume of the nanocomposite zeolite material accounts for more than 50%; And / or, the mass density of the nanocomposite zeolite material is 2.1-2.2 g / cc.
5. The method for preparing the nanocomposite zeolite material according to any one of claims 1 to 4, characterized in that: The preparation method comprises the following steps: fly ash is subjected to a two-stage fusion (melting, hydrothermal) zeolite synthesis process to prepare the nano composite zeolite material; Preferably, the fly ash includes but is not limited to one, two or more of the following sources: coal-fired power plants, waste incineration plants, boiler combustion sites, etc., such as ultrafine powder raw materials prepared from fly ash from fly ash landfills and boiler combustion residues; preferably, fly ash generated immediately by pulverized coal boilers in power plants is selected.
6. The preparation method according to claim 5, characterized in that: The process of the melting stage includes: mixing fly ash with alkali, heating and melting, grinding, and diluting to obtain a crystallization precursor solution; And / or, the process of the hydrothermal stage includes: aging and hydrothermal process to obtain crystals; preferably includes adding doping elements, aging and hydrothermal process to obtain crystals doped with elements; and / or, the hydrothermal stage may include repeated hydrothermal stages of adding N doping elements, N being an integer equal to or greater than 1, for example, N=1, 2, 3, 4, 5, 6, 7, 8, 9, 10; and / or, adding doping elements, preferably before the start of the hydrothermal process with N>1, to introduce designated elements so that these elements uniformly form highly active catalytic sites; And / or, the doping element is selected from one, two or more micronutrients required by plants: magnesium (Mg), iron (Fe), zinc (Zn), molybdenum (Mo), boron (B), selenium (Se), etc.; preferably, the doping element is introduced through a dopant, including but not limited to nanoparticles, alkaline substances and / or crystal nuclei of the one, two or more doping elements; And / or, the mass ratio of the dopant to the crystallization precursor solution is 1:(1-5).
7. The preparation method according to claim 5 or 6, characterized in that: The preparation method of the nanocomposite zeolite material comprises the following steps: (1) mixing fly ash and alkali, heating and melting, grinding, and diluting to obtain a crystallization precursor solution; (2) The crystallization precursor solution is subjected to a hydrothermal process to obtain the nanocomposite zeolite material. Alternatively, the method for preparing the nanocomposite zeolite material comprises the following steps: (1) mixing fly ash and alkali, heating and melting, grinding, and diluting to obtain a first crystal precursor solution; (2) the first crystal precursor solution is subjected to a hydrothermal process and filtered to obtain crystals and a first filtrate; (3) the first filtrate is mixed and diluted with a dopant containing element 1, and with or without adding a base as required, to obtain a second crystal precursor solution; the second crystal precursor solution is subjected to a hydrothermal process and filtered to obtain crystals containing element 1 and a second filtrate; (4) The filtrate obtained in the subsequent hydrothermal stage is treated according to step (3), the dopant contains element 2, and crystals containing element 2 and filtrate are obtained; until all the required doping elements are incorporated into the crystals; The element 1 and element 2 are the same or different, preferably different, and are both selected from the doping elements; The element 1 represents one, two or more elements; The element 2 represents one, two or more elements.
8. Use of the nanocomposite zeolite material according to any one of claims 1 to 4 as a sustained-release medium material, preferably as an agricultural sustained-release medium material.
9. A slow-release fertilizer, comprising the nanocomposite zeolite material according to any one of claims 1 to 4, wherein the nanocomposite zeolite material is used as a carrier of the active ingredient of the fertilizer; Preferably, the fertilizer active ingredients are macronutrient elements, such as N, P, K and / or S elements. Preferably, the slow-release fertilizer is obtained by immersing the nanocomposite zeolite material in a cationic solution containing active ingredients of the fertilizer; Preferably, the cations containing active fertilizer ingredients are provided by compounds such as ammonium nitrate, potassium nitrate, potassium phosphate, synthetic ammonia, urea and / or sodium nitrate. Preferably, the slow-release fertilizer may be a solid-liquid mixed fertilizer or a solid fertilizer.
10. A slow-release herbicide comprising the nanocomposite zeolite material according to any one of claims 1 to 4 and a herbicide.
11. Use of the slow-release fertilizer according to claim 9 or the slow-release herbicide according to claim 10 in fields such as soil and / or planting.
12. A soil fertilizer, comprising the nanocomposite zeolite material according to any one of claims 1 to 4; the soil fertilizer can be a liquid-solid mixed fertilizer or a solid fertilizer.
13. A soil conditioner, comprising the nanocomposite zeolite material according to any one of claims 1 to 4; the soil conditioner may be a liquid-solid mixed conditioner or a solid conditioner.
14. A plant fertilizer, comprising the nanocomposite zeolite material according to any one of claims 1 to 4; the plant fertilizer can be a liquid-solid mixed fertilizer or a solid fertilizer.
15. Use of the nanocomposite zeolite material according to any one of claims 1 to 4 in wastewater treatment.
16. A wastewater treatment agent comprising the nanocomposite zeolite material according to any one of claims 1 to 4.
17. A plant growth agent, comprising the nanocomposite zeolite material according to any one of claims 1 to 4.